Effects of Different Variants in the ENPP1 Gene on the Functional Properties of Ectonucleotide Pyrophosphatase/Phosphodiesterase Family Member 1. Issue 11 (23rd August 2016) - Stella, Jacqueline; Buers, Insa; van de Wetering, Koen; Höhne, Wolfgang; Rutsch, Frank; Nitschke, Yvonne
Abstract : Variants in ENPP1 are associated with generalized arterial calcification of infancy. We analyzed 13 putative pathogenic ENPP1 variants in vitro regarding their functional properties. One putative pathologic variant (c.2462 G>A, p.Arg821His) showed normal activity and would therefore be considered a polymorphism. Furthermore, we identified four mutants (c.1412A>G, p.Tyr471Cys; c.1510A>C, p.Ser504Arg; c.1976A>G, p.Tyr659Cys; c.2330A>G, p.His777Arg) with residual E‐NPP1 function, which would be potential therapeutical targets for conformational stabilizing agents. ABSTRACT: Ectonucleotide pyrophosphatase/phosphodiesterase family member 1 (E‐NPP1), encoded by ENPP1, is a plasma membrane protein that generates inorganic pyrophosphate (PPi ), a physiologic inhibitor of hydroxyapatite formation. In humans, variants in ENPP1 are associated with generalized arterial calcification of infancy, an autosomal‐recessive condition causing premature onset of arterial calcification and intimal proliferation resulting in stenoses. ENPP1 variants also cause pseudoxanthoma elasticum characterized by ectopic calcification of soft connective tissues. To determine the functional impact of ENPP1 missense variants, we analyzed 13 putative pathogenic variants in vitro regarding their functional properties, that is, activity, localization, and PPi generation. Transfection of eight of the 13 variants led to complete loss of NPP activity, whereas four mutants (c.1412A > G, p.Tyr471Cys; c.1510A > C, p.Ser504Arg; c.1976A > G, p.Tyr659Cys; c.2330A > G, p.His777Arg) showed residual activity compared with wild‐type E‐NPP1. One putative pathologic variant (c.2462 G > A, p.Arg821His) showed normal activity. The five mutants with normal or residual E‐NPP1 enzyme activity were still able to generate PPi and localized in the plasma membrane. In this study, we identified a functional ENPP1 polymorphism, which was expected to be pathogenic till now. Furthermore, we identified four mutants (p.Tyr471Cys, p.Ser504Arg, p.Tyr659Cys, p.His777Arg) with residual E‐NPP1 function, which would be potential therapeutical targets for conformational‐stabilizing agents.